Foreign direct investment and productivity spillovers: A firm-level analysis of Bangladesh in comparison with Vietnam - Md Arif-Ur-Rahman; Kazuo Inaba (Journal of Economic Structures, 2021)
Foreign direct investment (FDI) is expected to generate external effects - usually termed FDI spillovers - for a host country, and these spillovers are thought to have consequences on the productivity of domestic firms. Despite this strong expectation, the empirical findings on FDI spillover are still indecisive. This study examines firm-level panel data to determine the effects of FDI spillover on firms' productivity in Bangladesh in comparison to Vietnam. We consider both the horizontal and vertical (backward and forward) spillover effects of FDI. We find evidence that Bangladeshi firms gain productivity improvement through intra-industry or horizontal linkages, whereas Vietnamese firms gain through backward linkages. Our findings suggest that increases in foreign presence in the same industry for Bangladesh and in downstream industries for Vietnam are related with increase in output of domestic firms.
Keywords: F2; O1; O3; 330; Bangladesh; Foreign direct investments; Horizontal spillover; Vertical spillover; Vietnam